2019
DOI: 10.1021/acsami.8b20178
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Conductive Nanocomposite Hydrogels with High Stretchability, Self-Healing, Adhesiveness, and 3D Printability for Human Motion Sensing

Abstract: Self-healing, adhesive conductive hydrogels are of great significance in wearable electronic devices, flexible printable electronics, and tissue engineering scaffolds. However, designing self-healing hydrogels with multifunctional properties such as high conductivity, excellent mechanical property, and high sensitivity remains a challenge. In this work, the conductive self-healing nanocomposite hydrogels based on nanoclay (laponite), multiwalled carbon nanotubes (CNTs), and N-isopropyl acrylamide are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
292
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(297 citation statements)
references
References 73 publications
4
292
0
1
Order By: Relevance
“…Based on the higher conductivity of rGO than graphene oxide, it was chosen as a component to prepare these HA‐DA/rGO hydrogels. It has been reported that the conductive materials could accelerate the wound healing process . Therefore, the conductivity of these hydrogels was tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the higher conductivity of rGO than graphene oxide, it was chosen as a component to prepare these HA‐DA/rGO hydrogels. It has been reported that the conductive materials could accelerate the wound healing process . Therefore, the conductivity of these hydrogels was tested.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the conductive materials could accelerate the wound healing process. [48][49][50][51][52] Therefore, the conductivity of these hydrogels was tested. The dried HA-DA/rGO0 hydrogel presented the lowest conductivity of 0.3 × 10 −4 S m −1 .…”
Section: Conductivity and Antioxidant Ability Of Ha-da/rgo Hydrogelmentioning
confidence: 99%
“…Significant contributions have been made concerning stimuli‐responsive hydrogels based on nanoclay‐incorporated copolymers. [ 76,132,154,158 ] Yao et al [ 76 ] reported on fabrication of self‐assembled thermoresponsive nanocomposite hydrogels based on poly( N ‐isopropylacrylamide‐ co ‐acrylamide)/laponite. The prepared nanocomposite bilayer hydrogels exhibited a high extent of elongation and temperature‐responsive swelling/deswelling characteristics even after many repeating cycles.…”
Section: Biomedical Applications Of Copolymer/clay Nanocompositesmentioning
confidence: 99%
“…[ 77 ] The responsive behavior of the copolymer/clay nanocomposite hydrogels is due to many factors such as phase transition temperature (LCST and UCST), inter/intra molecular hydrogen bond interaction, type of crosslinking, density and protonation–deprotonation of side/pendant groups of the polymer chains. [ 98,102,158 ] Smart hydrogels can be used in biomimetic soft robotics for vehicles, drug delivery, manipulators, and actuators. [ 159 ] On the other hand, nanocomposite hydrogels have been used in regenerative medicine as a cell/protein/drug delivery carrier, as soft implants, and scaffolds due to their exceptional physical and biological characteristics.…”
Section: Biomedical Applications Of Copolymer/clay Nanocompositesmentioning
confidence: 99%
“…Specifically, with the growing demand of biomaterials and wearable equipment, electrically conductive hydrogels (CHs) with electrical conductivity and flexible mechanical properties have attracted great interest [9]. CHs have many excellent properties, such as strong adhesion, high porosity, good swelling and biocompatibility, which can transform external stimuli into recorded electrical signals [10][11][12]. Therefore, CHs have been widely used in the preparation of human motion sensor.…”
Section: Introductionmentioning
confidence: 99%